Flavor enhancers in growing-pig rations - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1976)
Groups of growing pigs restricted to control feed or feed containing one of 5 commercial flavoring agents or taste enhancers consumed similar amounts of feed and made similar weight gains and similar feed/gain.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Flavor enhancers; Weight gain; Feed/gain ratio